Persistence of Trypanosoma brucei as early procyclic forms and social motility are dependent on glycosylphosphatidylinositol transamidase. Issue 4 (10th January 2022) - Knüsel, Sebastian; Jenni, Aurelio; Benninger, Mattias; Bütikofer, Peter; Roditi, Isabel
Abstract: Glycosylphosphatidylinositol (GPI)‐linked molecules are surface‐exposed membrane components that influence the infectivity, virulence and transmission of many eukaryotic pathogens. Procyclic (insect midgut) forms of Trypanosoma brucei do not require GPI‐anchored proteins for growth in suspension culture. Deletion of Tb GPI8, and inactivation of the GPI:protein transamidase complex, is tolerated by cultured procyclic forms. Using a conditional knockout, we show Tb GPI8 is required for social motility (SoMo). This collective migration by cultured early procyclic forms has been linked to colonization of the tsetse fly digestive tract. The SoMo‐negative phenotype was observed after a lag phase with respect to loss of Tb GPI8 and correlated with an unexpectedly slow loss of procyclins, the major GPI‐anchored proteins. Procyclins are not essential for SoMo, however, suggesting a requirement for at least one other GPI‐anchored protein. Loss of Tb GPI8 initiates the transition from early to late procyclic forms; this effect was observed in a subpopulation in suspension culture, and was more pronounced when cells were cultured on SoMo plates. Our results indicate two, potentially interlinked, scenarios that may explain the previously reported failure of Tb GPI8 deletion mutants to establish a midgut infection in the tsetse fly: interference with stage‐specific gene expression and absence of SoMo. Abstract : The attachment of GPI anchors to proteins is catalysed by transamidases. Tb GPI8, a transamidase subunit of Trypanosoma brucei, is not essential for growth of procyclic (insect midgut) forms. However, its depletion in culture results in reduced social motility and loss of markers of early procyclic forms. These phenotypes can be explained by the lack of one or more surface proteins that might function as parasite‐derived ligands, receptors, regulators of signalling pathways, enzymes or lubricant molecules.